La nouvelle dynamique de la politique commerciale aux États-Unis et l'Accord de libre-échange nord-américain - Martin, Pierre (Études internationales, 1993)
Given the disparities in economic development between the United States and Mexico, and in light of the controversies that such a negotiation was bound to generate, the American decision to negotiate a North American Free Trade Agreement (NAFTA) has come as a surprise to many. This article proposes elements of an explanation for this American decision. The analysis proceeds at three levels: the international System, societal pressures, and the state. The analysis of coalition politics in the NAFTA policymaking process leads to two main conclusions. First, the political dynamic of NAFTA was similar to that which led to a strategy of « aggressive unilateralis » in u.s. trade policy in the late 1980s. Second, the analysis points to international investment ties as a key mechanism linking international structural change to domestic political response.